PLUMBIAN "ALUNITES" IN HYDROTHERMAL ALTERATION ZONES OF EPITHERMAL AND PORPHYRY TYPE MINERALIZATIONS IN W. THRACE - Βουδούρης Π.; Αρίκας Κ.; Κατερινόπουλος Α. (Bulletin of the Geological Society of Greece, 2004)
In this study a new occurrence of Pb-rich members of the alunite supergroup minerals is described. The "alunites" were traced in advanced argilic alteration zones of epithermal and porphyry type mineralizations in W. Thrace/(Greece). These "alunites" are Ca-Sr-Ba-Pb-rich phosphatessulfates and represent solid solutions between members of the alunite, woodhouseite and crandallite group minerals. The highest concentrations of PbO in the Mavrokoryfi and Melitaina alunites are 24.7% and 17.4% respectively. The plumbian phosphates-sulfates occur in the cores of the crystals and are surrounded by common K-Na-rich alunites in Mavrokoryfi and Ba-rich woodhouseite in Melitena, an indication that they were formed in a magmatic-hydrothermal environment after dissolution of apatite and feldspars by phosphate-sulphate rich solutions. The mineral-chemistry of these "alunites" can provide information regarding the genesis of the advanced argilic alteration zones in Greece, and help us in the distinction of the epithermal from deep porphyry style environments.